(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Rabies remains a serious public health problem in more than 150 countries and territories, with a 100% case fatality rate once clinical disease develops. Recently, it has re-emerged in Ca Mau Province and Phu Tan Commune. Objectives: This study aimed to determine the proportion of correct knowledge, attitudes, and practices (KAP) regarding rabies prevention and control, and to identify associated factors among dog and/or cat owners in Phu Tan commune, Ca Mau province in 2025. Materials and Methods: A cross-sectional descriptive study was conducted among 756 household representatives who owned dogs and/or cats from July to December 2025. Results: The proportions of respondents with correct knowledge, appropriate attitudes, and correct practices were 63.2%, 63.4%, and 46.7%, respectively. Multivariable logistic regression analysis showed statistically significant associations (p<0.05). Factors associated with knowledge included age group, educational level, purpose of raising dogs/cats, economic status, and history of rabies exposure. Attitudes were associated with educational level, occupation, economic status, and knowledge. Practices were associated with age group, educational level, occupation, purpose of raising dogs/cats, and knowledge. Respondents with correct knowledge were 3.5 times more likely to have appropriate attitudes and 3.2 times more likely to have correct practices compared to those without correct knowledge. Conclusions: The findings suggest the need to strengthen health education and communication to improve knowledge, attitudes, and practices regarding rabies prevention and control in the community, particularly among high-risk groups.